Campaign Governance and Partnerships: Unraveling COVID-19 Vaccine Promotion Efforts in China’s Neighborhoods - Yang R; Sun S (Risk Management and Healthcare Policy, 2023)
Ronghui Yang, Sirui Sun Department of Public Administration, College of Humanities, Donghua University, Shanghai, 200051, People’s Republic of ChinaCorrespondence: Sirui Sun, Department of Public Administration, College of Humanities, Donghua University, 1882 West Yan’an Road, Shanghai, 200051, People’s Republic of China, Tel +8618521057816, Email sirui_sun@dhu.edu.cnBackground: COVID-19 vaccine promotion helps counter vaccine hesitancy and raise vaccine acceptance. Therefore, the Chinese state created collaborative infrastructures of COVID-19 vaccine promotion programs to promote stakeholder engagement and unload the burden of policy practitioners. However, partnerships in COVID-19 vaccine promotion programs have been underrepresented.Methods: To address this lacuna, we qualitatively explored how partnerships in the COVID-19 vaccine promotion campaign (CVPC) were organized in China’s neighborhoods. Specifically, we recruited participants via personal networks, referrals from acquaintances, and snowballing approaches, and conducted the qualitative thematic analysis following interviews with 62 Chinese stakeholders.Results: This study indicates that to promote partnerships in CVPCs, neighborhood managers formed leadership in CVPCs, expanded the collaborative network, trained Health Promotion Practitioners (HPPs), and coordinated with HPPs to shape partnership agreements, produced COVID-19 vaccine promotional materials and advertised COVID-19 vaccines via diverse media tools. Although coproduction of CVPCs to a certain extent promoted state-society interaction in neighborhoods and state responsiveness to public demands, partners’ disagreements on strategies applied by states for promoting COVID-19 vaccines eroded partnerships in CVPCs.Conclusion: To construct a robust partnership in CVPCs, depoliticizing CVPCs and creating shared values among stakeholders in CVPCs are expected. Our study will not only deepen global audiences’ understanding of CVCPs in China but also offer potential neighborhood-level solutions for implementing local and global health promotion efforts.Keywords: campaign governance, partnerships, COVID-19 vaccine promotion, neighborhood, China